2015 IEEE Aerospace Conference 2015
DOI: 10.1109/aero.2015.7119247
|View full text |Cite
|
Sign up to set email alerts
|

Subsystem support feasibility for formation flight measuring Bi-directional Reflectance

Abstract: Distributed Spacecraft Missions can be used to improve science performance in earth remote sensing by increasing the sampling in one or more of five dimensions: spatial, temporal, angular, spectral and radiometric. This paper identifies a gap in the angular sampling abilities of traditional monolithic spacecraft and proposes to address it using small satellite clusters in formation flight. The angular performance metric chosen to be Bi-directional Reflectance Distribution Function (BRDF), which describes the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The corresponding equations (also COWPOKE) are more complex than (8 and have not been analyzed in this paper. Parallel literature [11], [13] has shown that slightly eccentric orbits are beneficial in compensating for the drift in the along track direction and aid in keeping the formation together after 7-8 months of operation. It would be valuable to find the optimal chief and differential eccentricity that would allow a good azimuthal spread via free orbit ellipses as well as be beneficial to maintain.…”
Section: Figure 12: Free Orbit Ellipse With 3+1 Satellites Simulatedmentioning
confidence: 60%
See 4 more Smart Citations
“…The corresponding equations (also COWPOKE) are more complex than (8 and have not been analyzed in this paper. Parallel literature [11], [13] has shown that slightly eccentric orbits are beneficial in compensating for the drift in the along track direction and aid in keeping the formation together after 7-8 months of operation. It would be valuable to find the optimal chief and differential eccentricity that would allow a good azimuthal spread via free orbit ellipses as well as be beneficial to maintain.…”
Section: Figure 12: Free Orbit Ellipse With 3+1 Satellites Simulatedmentioning
confidence: 60%
“…Different inclinations cause the J2 forces on each satellite to be different causing the RAAN to rotate differently. A 20 deg view zenith angle spread takes less than 3 months to break up [11] because increasing RAAN differential causes the angular spread at the poles to decrease and equator to increase and eventually the latter is too large for the satellites to see each other. Figure 15 shows a drift not only in the along-track direction (as seen in Figure 14) but also in the radial direction, indicative of the formation breaking (similar to semi major axis difference).…”
Section: Figure 12: Free Orbit Ellipse With 3+1 Satellites Simulatedmentioning
confidence: 99%
See 3 more Smart Citations